Optimalisasi Efesiensi Bisnis Organisasi Melalui Pemanfaatan Sistem Dan Teknologi Informasi - Noor Adinda S.F. Lubis; Muhammad Irwan Padli Nasution (Pusat Riset dan Inovasi Nasional, 2023)
The use of information systems and technology has become a central element in efforts to increase business efficiency in today's organizational environment. Organizations must understand that operational efficiency is a very valuable asset in achieving their business goals. By wisely utilizing information systems and technology, you can automate business processes, increase access to information, improve internal communications, and make effective decision making easier. This research aims to explain how the use of information systems and technology can be optimized to increase organizational business efficiency.